Enhancing academic resilience through mindfulness training: an experimental study with Chinese undergraduates and the mediating role of psychological flexibility - Yuan, Ming; Hu, Zhe (Frontiers in Psychology, 2025)
IntroductionThis study investigates the impact of mindfulness on academic resilience among university students, with a particular focus on the mediating roles of self-compassion and psychological flexibility.MethodsUsing a post-test-only control group experimental design, 200 undergraduate students from a Chinese university were randomly assigned to either an intervention group, which received a four-week mindfulness training program, or a control group. Data were collected after the intervention using validated self-report instruments and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM).ResultsThe results revealed that mindfulness significantly enhanced both self-compassion and psychological flexibility, which in turn positively predicted academic resilience. Parallel mediation analysis confirmed that both self-compassion and psychological flexibility independently mediated the relationship between mindfulness and academic resilience, with stronger effects observed in the intervention group. Multi-group analysis further demonstrated significant differences in structural path strengths between the two groups, confirming the effectiveness of the mindfulness intervention.DiscussionThese findings offer theoretical support for process-based models of resilience and emotion regulation and provide practical insights into scalable, low-cost interventions for enhancing student well-being in higher education. In addition, the study highlights culturally grounded evidence from a Chinese higher education context, addressing the relative scarcity of experimental investigations on mindfulness and resilience in non-Western settings. Limitations include the reliance on self-reported data, the use of a single-institution sample, and the short intervention period, which may constrain generalizability and long-term inference. Nevertheless, the findings support the relevance of mindfulness-based training as a culturally adaptable and resource-efficient approach to strengthening academic resilience in university populations.